The Role of Nutritional Therapy in Inhibiting the Progression of Chronic Kidney Disease: A Narrative Literature Review - Harnavi Harun; Genta Pradana (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
The need for proper nutrition and diet is fundamental in every stage of chronic kidney disease. The principle of nutritional therapy is slowing the progression of chronic kidney disease, delaying patients with CKD (chronic kidney disease) from getting kidney replacement therapy. In CKD patients, there is a disturbance of protein homeostasis, disturbance in metabolism protein, acid-base disorders, and hormonal dysfunctions. As the progression of CKD increases, nitrogen-containing products accumulate, causing a decrease in appetite. In CKD patients, intestinal absorption is also impaired because uremia causes microbiota disturbance and damage to the intestinal epithelium. These various things cause nutritional status to become often irregular, and protein energy wasting frequently occurs, thus requiring dietary adjustments in patients with CKD. In conclusion, each individual with CKD has a different nutritional therapy approach depending on the disease conditions and nutritional status of the individual. Appropriate nutritional therapy in CKD patients can reduce disease progression.